Assessing post-harvest labor shortages, wages, and welfare - Andrew J. Cassey; Kwanyoung Lee; Jeremy Sage; Peter R. Tozer (Agricultural and Food Economics, 2018)
For horticultural commodities, labor is necessary for post-harvest activities such as management, marketing, packing, and distribution. We create a model with pre- and post-harvest tasks and transportation network to study how a shortage in the pre-harvest labor market affects the post-harvest labor market and downstream commodity markets. Parameterized to U.S. pome and prunus industries, we find output prices are 16% greater, the prunus industry does less well adjusting, and producers benefit despite output reductions. Producers' benefit comes almost exclusively from higher prices, but decreases when the resulting post-harvest labor shortage increases spoilage along the transportation network.
Keywords: J43; Q13; 330; Post-harvest; Labor shortage; Transportation; Pome; Prunus; Welfare